CSR IMPLEMENTATION OF COAL MINING COMPANY - Warman Warman (AKUNTABEL, 2013)
Coal mining activities in addition to the positive impact too negatively in the form of social conflict and environmental damage in the area. Therefore the program Corporate Social Responsibility (CSR) is very important in order to respond to the problem. Law No. 40 of 2007 on limited liability, set about corporate social responsibility, as a must do. CSR implementation, integrated in every stage of the operational activities of the company. The results showed that the implementation of CSR PT. JMB is: (1) the company commitment to the program pretty well comdev characterized by a clear organizational structure management, and a willingness to allocate funds set of production, (2) Sustainability CSR program in general is not optimal, the indicator: many programs designed partially, or not planned for sustainability so that less benefit improvements and changes, as well as the independence of the community, (3) Concrete results of the CSR activities of the company shows that the positive perception of CSR programs running strong as well and vice versa soon develop a negative perception because of the planned program was not realized. It also deals with the public perception that CSR is the right of people because of the negative impact of the company's operations. From this research it is necessary to develop future CSR programs that are sustainable, well planned and implemented so that the community empowerment and independence, can be realized in line with expectations and ideals of CSR.Keywords: Implementation of Corporate Social Responsibility (CSR)